2013
DOI: 10.1371/journal.pone.0055554
|View full text |Cite
|
Sign up to set email alerts
|

PTS1 Peroxisomal Import Pathway Plays Shared and Distinct Roles to PTS2 Pathway in Development and Pathogenicity of Magnaporthe oryzae

Abstract: Peroxisomes participate in various important metabolisms and are required in pathogenicity of fungal plant pathogens. Peroxisomal matrix proteins are imported from cytoplasm into peroxisomes through peroxisomal targeting signal 1 (PTS1) or peroxisomal targeting signal 2 (PTS2) import pathway. PEX5 and PEX7 genes participate in the two pathways respectively. The involvement of PEX7 mediated PTS2 import pathway in fungal pathogenicity has been documented, while that of PTS1 remains unclear. Through null mutant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 70 publications
6
85
0
Order By: Relevance
“…In M. oryzae , mutants with abnormal peroxisomes such as ΔMopex6 [30], ΔMopex5 [34], ΔMopex7 [33], and ΔMopex19 [41] showed inability to metabolize fatty acids and NaAC. In addition, yeast Δsnf1 and Δsnf4 were reported to be devoid of peroxisomal structures [38].…”
Section: Resultsmentioning
confidence: 99%
“…In M. oryzae , mutants with abnormal peroxisomes such as ΔMopex6 [30], ΔMopex5 [34], ΔMopex7 [33], and ΔMopex19 [41] showed inability to metabolize fatty acids and NaAC. In addition, yeast Δsnf1 and Δsnf4 were reported to be devoid of peroxisomal structures [38].…”
Section: Resultsmentioning
confidence: 99%
“…Nile red staining and fluorescein diacetate (FDA) staining were performed as previously described [33], and the fluorescence was observed under an Olympus Xa21 fluorescent microscope with filters adapted to excitation 495 nm and emission 520 nm. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In M. oryzae , MoPEX5 and MoPEX6 had been identified to participate in PTS1 matrix protein import2629. MoPEX7 contributes to the import of PTS2 matrix proteins30. Recently, it has been reported that the imports of PTS1- and PTS2-containing matrix proteins were impaired in the ΔMopex19 mutants31.…”
Section: Discussionmentioning
confidence: 99%
“…In C. lagenarium , the deficiency of peroxisomal function in the ΔClpex6 mutants leads to its inability to utilize long-chain fatty acids2425. In M. oryzae, the peroxisome-related mutants, ΔMopex5, ΔMopex6, and ΔMopex7, were unable to utilize long-chain fatty acids as sole carbon sources and ΔMopex19 mutants showed severe growth reduction when cultured with long-chain fatty acids26293031. Moreover, yeast cells deficient in Pex1 also show a characteristic phenotype with the inability to grow on oleic acid as sole carbon source4344.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation